In Vitro Activities of Doripenem, a New Broad-Spectrum Carbapenem, against Recently Collected Clinical Anaerobic Isolates, with Emphasis on the Bacteroides fragilis Group - Snydman, David R. (American Society for Microbiology (ASM), 2008)
Doripenem was evaluated against 527 recent clinical isolates, i.e., 404 Bacteroides fragilis isolates and 123 gram-positive anaerobe isolates. Against B. fragilis, doripenem was as active as imipenem, meropenem, and piperacillin-tazobactam and more active than ertapenem or ampicillin-sulbactam. Doripenem was active against isolates resistant to ertapenem, ampicillin-sulbactam, cefoxitin, clindamycin, and moxifloxacin. All of the gram-positive isolates tested were susceptible to doripenem.